1995
DOI: 10.1074/jbc.270.29.17407
|View full text |Cite
|
Sign up to set email alerts
|

Isoform Cloning, Actin Binding, and Chromosomal Localization of Human Erythroid Dematin, a Member of the Villin Superfamily

Abstract: Dematin is an actin-bundling protein of the erythroid membrane skeleton and is abundantly expressed in human brain, heart, skeletal, muscle, kidney, and lung. The 48-kDa subunit of dematin contains a headpiece domain which was originally identified in villin, and actin-binding protein of the brush-border cytoskeleton. The head-piece domain of villin is essential for its morphogenic function in vivo. Here we report the primary structure of 52-kDa subunit of dematin which differs from the 48-kDa subunit by a 22-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 23 publications
2
70
0
Order By: Relevance
“…Our previous biochemical and genetic characterization of dematin has shown that both 48-and 52-kDa subunits of dematin contain a C-terminal headpiece domain that is homologous to the headpiece domain of villin (10,23). The 383-residue, 48-kDa subunit consists of an N-terminal core domain that includes a proline-rich motif (PEST), a polyacidic motif, and a C-terminal 75-residue headpiece domain (23).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous biochemical and genetic characterization of dematin has shown that both 48-and 52-kDa subunits of dematin contain a C-terminal headpiece domain that is homologous to the headpiece domain of villin (10,23). The 383-residue, 48-kDa subunit consists of an N-terminal core domain that includes a proline-rich motif (PEST), a polyacidic motif, and a C-terminal 75-residue headpiece domain (23).…”
Section: Discussionmentioning
confidence: 99%
“…Based on sequence of 48-kDa and 52-kDa subunits, a model has been proposed where the headpiece domain plays a critical role in the assembly of dematin trimer (10). We used a well-established chemical crosslinking approach to test whether the deletion of dematin headpiece domain disrupts the formation of trimer and influences dematin's ability to interact with its surrounding cytoskeletal components (11,24).…”
Section: Headpiece Domain Is Required For the Assembly Of Dematin Trimentioning
confidence: 99%
See 2 more Smart Citations
“…Dematin is a known actin filament bundling protein that is not known to play a role in splicing [47]. The protein, p47 is similar to a zinc finger protein (Zfp462), but the function of this protein is not known (Swissprot database).…”
Section: Discussionmentioning
confidence: 99%